The Owl, the Nightingale and the Jew in the Thorn-bush: Relocating Anti-Semitism in Die Meistersinger. (20th June 2016) - Grey, Thomas; Paige, Kirsten
Abstract: For the past twenty-five years a key piece of evidence for an anti-Semitic subtext in Wagner's Die Meistersinger has been identified in the Grimm Brothers' anti-Semitic tale 'The Jew in the Thorn-bush' and a possible allusion to this in the text of Walther's Act I 'trial song'. This article argues that the passages in question are better explained with reference to a medieval poetic tradition still prevalent in nineteenth-century German culture involving the vocal contest between birds, paradigmatically the owl and the nightingale. Since the twelfth century, the owl and the nightingale have debated the merits of high and low art, religious themes, social forms, poetic diction and more. The associations of pedantry and harsh, coarse vocal character with the figure of the owl maps readily onto the negative traits of Beckmesser, just as the contrasting associations of the melodious nightingale with springtime, courtship and 'natural' musicality align with traits of Wagner's artist-hero, Walther von Stolzing. Rather than displacing the possible anti-Semitic reading of Beckmesser, however, this alternative reading of the Beckmesser–Walther antagonism through the lens of avian conflict or debate poetry relocates that reading within a broader discursive and figurative context, one that is more commensurate with the possible role of anti-Semitic subtexts within Wagner's music dramas in general.